Reconstruction of Mandatory Bequest (Wasiat Wajibah) in the Compilation of Islamic Law: Legal Protection for Out-of-Wedlock Children in Indonesia - Patria Utama, Adi Fadli, Khairul Hamim, Jumarim (Lembaga Bale Literasi, 2025)
The study examines the reconstruction of wasiat wajibah (mandatory bequest) within the Compilation of Islamic Law (KHI) as a legal mechanism for strengthening the protection of out-of-wedlock children in Indonesia. The research employs a qualitative socio-legal approach through document analysis and in-depth interviews with Religious Court judges to explore contemporary judicial developments, constitutional principles, and Islamic legal objectives relevant to inheritance rights. The findings indicate that the current formulation of Article 209 KHI, which limits wasiat wajibah to adopted children and adoptive parents, is no longer sufficient to accommodate contemporary legal realities and the increasing recognition of children's rights. Judicial practice demonstrates a progressive expansion of wasiat wajibah beneficiaries beyond the categories explicitly regulated in the KHI, including non-Muslim relatives, stepchildren, legally excluded heirs, and out-of-wedlock children. These developments reflect a growing emphasis on substantive justice, social welfare, and child protection within Indonesian Islamic family law. The study further reveals that judges generally support legal reforms aimed at protecting the economic interests of out-of-wedlock children, provided that such reforms remain consistent with the fundamental principles of Islamic inheritance law. Based on these findings, the study proposes the reconstruction of Article 209 KHI by explicitly recognizing the right of out-of-wedlock children who can legally establish a biological relationship with the deceased to receive wasiat wajibah not exceeding one-third of the inheritance estate. The proposed reconstruction is grounded in constitutional guarantees of child protection, the principle of non-discrimination, the best interests of the child, and the objectives of Islamic law (maq??id al-shar?‘ah), particularly the protection of lineage (?if? al-nasl), property (?if? al-m?l), and public welfare (ma?la?ah). The study concludes that reformulating Article 209 KHI would enhance legal certainty, promote substantive justice, and strengthen the legal protection of out-of-wedlock children while preserving the normative foundations of Islamic inheritance law.